2009
DOI: 10.1016/j.yexcr.2009.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion and transcellular migration of neutrophils and B lymphocytes on fibroblasts

Abstract: During tissue inflammation, infiltrated leukocytes may have physical contacts with fibroblasts.We observed that neutrophils and B lymphocytes adhered in a larger proportion than T cells on cultured fibroblasts. Microscopy showed that adhesion was also characterized by leukocyte engulfment by the fibroblasts. In migration assays, only neutrophils and B lymphocytes were selectively able to migrate through a fibroblast barrier. Adhesion and migration were increased by stimulation with tumor necrosis factor-α (TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 56 publications
0
16
0
2
Order By: Relevance
“…This step depends initially on chemokine secretion and ICAM-1 and VCAM-1 expression at the inflammation site (Kukielka et al, 1993; Cook-Mills et al, 2011). Couture et al (2009), have shown that TNF-α and PMA increase neutrophil recruitment by CF. Previous results from our laboratory have shown that in CF, TLR4 activation by LPS, induces monocyte recruitment by CF themselves, due initially to the monocyte migration favored by MCP-1 secretion; whereas ICAM-1 and VCAM-1 expression in turn favors monocyte adhesion (Humeres et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…This step depends initially on chemokine secretion and ICAM-1 and VCAM-1 expression at the inflammation site (Kukielka et al, 1993; Cook-Mills et al, 2011). Couture et al (2009), have shown that TNF-α and PMA increase neutrophil recruitment by CF. Previous results from our laboratory have shown that in CF, TLR4 activation by LPS, induces monocyte recruitment by CF themselves, due initially to the monocyte migration favored by MCP-1 secretion; whereas ICAM-1 and VCAM-1 expression in turn favors monocyte adhesion (Humeres et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…An alternative explanation is that fibroblast-derived mediators are more attractive to B-cells than T-cells. For example, it has been reported that B-cells adhere more efficiently to human dermal fibroblasts than T-cells (Couture et al, 2009). Moreover, B-cells, but not T-cells, were able to migrate through a fibroblast barrier (monolayer) (Couture et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that B-cells adhere more efficiently to human dermal fibroblasts than T-cells (Couture et al, 2009). Moreover, B-cells, but not T-cells, were able to migrate through a fibroblast barrier (monolayer) (Couture et al, 2009). In fact in that study the fibroblasts appeared to selectively promote B-cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia, TNF-α, IL-1β, and LPS have been shown to induce expression of ICAM-1 on the vascular endothelial surface [81,109,123]. VCAM-1 and ICAM-1 interact with alpha-4 integrin (VLA-4) expressed on B-lymphocytes, and beta-2 integrins expressed on neutrophils and monocytes/macrophages resulting in extravasation [124,125].…”
Section: Vascular Dysfunctionmentioning
confidence: 99%